Planning waste cooking oil collection systems - Ramos, T. (2014)
This research has been motivated by a real-life problem of a waste cooking oil collection system characterized by the existence of multiple depots with an outsourced vehicle fleet, where the collection routes have to be plan. The routing problem addressed allows open routes between depots, i.e., all routes start at one depot but can end at the same or at a different one, depending on what minimizes the objective function considered. Such problem is referred as a Multi-Depot Vehicle Routing Problem with Mixed Closed and Open Inter-Depot Routes and is, in this paper, modeled through a mixed integer linear programming (MILP) formulation where capacity and duration constraints are taken into account. The model developed is applied to the real case study providing, as final results, the vehicle routes planning where a decrease of 13% on mileage and 11% on fleet hiring cost are achieved, when comparing with the current company solution.